Right ventricular strain: Cardiovascular challenges in pulmonary diseases - Rahmianti, Nia; Vendarani, Yoni; Maulidiyah, Novita (PT. DEKA RESEARCH INSTITUTE, 2024)
Right heart failure is associated with a poor prognosis, and right ventricular (RV) strain, assessed through echocardiography, is a valuable method for evaluating right heart function. However, discussions on this topic remain limited. This article explores RV strain induced by pulmonary diseases to increase awareness of how these conditions can exacerbate right heart failure. Pulmonary embolism leads to increased RV afterload, resulting in RV dilation and ischemia, which can progress to cardiogenic shock. Echocardiography is effective in detecting RV strain and assessing the severity of pulmonary embolism. In Chronic Obstructive Pulmonary Disease (COPD), increased pulmonary vascular resistance causes RV dysfunction, identifiable through speckle-tracking echocardiography (STE). Pulmonary fibrosis may contribute to right heart failure through pulmonary hypertension. RV Longitudinal Strain (RVLS) is an important prognostic marker in patients with pulmonary hypertension and COVID-19, where low RVLS (≤20.5%) is associated with higher mortality. In conclusion, right heart failure carries a poor prognosis, and RV strain evaluation using STE is a useful tool for early detection. Pulmonary diseases, including COPD, pulmonary embolism, pulmonary fibrosis, pulmonary hypertension, and COVID-19, can induce RV strain, which is critical for assessing prognosis and guiding disease management.